The genesis of Persian and Urdu languages and literatures in India - Islam, Arshad (International Islamic University Malaysia, 2015)
The Indian subcontinent has contained a vast array of ethnicities, cultures, traditions and languages since the beginning of civilisation. While classical Indian civilisation was based on Sanskrit, the sacerdotal language of the Brahmins, this sacred language did not affect the general mass of people, nor literature beyond a privileged elite. The first true lingua franca that transcended caste barriers to a certain extent was Persian, which was adopted by the ruling dynasties of Muslim India (who themselves were generally Turks or indigenous Indians rather than Persians), their Hindu peers, as well as the civil servants. However, from the beginning of the seventeenth century Urdu began to form around the lower echelons of society as a pidgin common tongue to enable communication between the myriad ethnicities of the Mughal Empire, ultimately restricting Persian to a refined language of culture and courtly life in the Mughal court and becoming a vibrant and dynamic language in its own right, thus becoming the first literary language with a substantial original contribution from Indians since ancient Sanskrit. This article charts the adoption of Persian and later the emergence of Urdu as spoken and literary languages in the Indian subcontinent using original sources in those languages.